Blue smoke and murder - Lowell, Elizabeth, 1944- (William Morrow, 2008)
Protecting a river guide with ties to the art world, private information collector and reluctant bodyguard Zach Balfour realizes his charge is in more danger than previously known, a situation that pits them against the ruthless multi-million-dollar Western art circuit.